Hubungan Antara Sumber Informasi Tentang HIV/AIDS Dengan Pemeriksaan Pencegahan Penularan HIV Dari Ibu Ke Anak (PPIA) Di Puskesmas II Denpasar Selatan - Ni Luh Putu Sri Erawati; Ni Ketut Somoyani; Ni Nyoman Suindri (Poltekkes Kemenkes Denpasar, 2018)
Transmission of HIV from infected mothers to their babies tends to increase. Prevention Mother-to-Child HIV Transmission (PMTCT) is one of the most effective interventions to prevent HIV transmission. This study aims to determine the relationship between information sources about HIV / AIDS with Prevention Mother-to-Child HIV Transmission (PMTCT) at Puskesmas II Denpasar Selatan from August to October 2017. The research design was observational by using cross-sectional design on pregnant women who perform antenatal care. Data analysis by Chi-square test. The results showed that the main source of information from Respondent in obtaining knowledge about HIV/AIDS was majority from health worker (30.0%). Most of the respondents had done PMTCT (71,7%). Sources of information have a significant and practical relationship statistically to the Prevention Mother-to-Child HIV Transmission (PMTCT)with OR of 3.167 (95% CI: 0.78 - 12.8). There is no correlation between information source about HIV / AIDS with Prevention Mother-to-Child HIV Transmission (PMTCT)to pregnant mother at Public Health Centre II South Denpasar with value p = 0,200 and value OR = 3,167 with significance level 95% (α = 0,05). From this research recommended that Public Health Centre officers provide information sources and motivate pregnant women to do Mother-to-Child HIV test.